Bioethanol production from hydrothermal pretreated wheat straw by a flocculating Saccharomyces cerevisiae strain : effect of process conditions - Ruíz, Héctor A. (2012)
Wheat straw is nowadays being considered a potential lignocellulose raw material for fuel ethanol production of second generation and as an alternative to conventional fuel ethanol production from cereal crops. In the present study, hydrothermal pretreated wheat straw with high cellulose content (>60%) at 180 °C for 30 min was used as substrate in simultaneous saccharification and fermentation (SSF) process for bioethanol production using a thermotolerant flocculating strain of Saccharomyces cerevisiae CA11. In order to evaluate the effects of temperature, substrate concentration (as effective cellulose) and enzyme loading on: (1) ethanol conversion yield, (2) ethanol concentration, and (3) CO2 concentration a central composite design (CCD) was used. Results showed that the ethanol conversion yield was mainly affected by enzyme loading, whereas for ethanol and CO2 concentration, enzyme loading and substrate concentration were found to be the most significant parameters. The highest ethanol conversion yield of 85.71% was obtained at 30 °C, 2% substrate and 30 FPU of enzyme loading, whereas the maximum ethanol and CO2 concentrations (14.84 and 14.27 g/L, respectively) were obtained at 45 °C, 3% substrate and 30 FPU of enzyme loading, corresponding to an ethanol yield of 82.4%, demonstrating a low enzyme inhibition and a good yeast performance during SSF process. The high cellulose content obtained in hydrothermal pretreatment and the use of a thermotolerant flocculating strain of S. cerevisiae in SSF suggest as a very promising process for bioethanol production.